2017
DOI: 10.1016/j.jvs.2017.05.113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative anemia and baseline cardiac risk on serious adverse outcomes after major vascular interventions

Abstract: Postoperative anemia increases the rate of early postoperative mortality and major ischemic events, particularly in patients at higher baseline cardiac risk. It also adversely affects respiratory complications and ICU LOS. Until a randomized trial definitively settles the issue, restrictive transfusion strategies should be practiced with caution in patients undergoing major vascular interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…26 We found that nadir Hb below 9.0 g/dL was associated with a higher risk of composite adverse events, even after stratifying patients by whether or not they received transfusions, what type of operation they had, or other confounders. This result suggests that above 9.0 g/dL may be the optimal Hb level for this population of patients, consistent with a previous report 27 that the inflection point in the incidence of composite outcomes lay around nadir Hb 9.0 g/dL for patients undergoing major vascular operation.…”
Section: Commentsupporting
confidence: 91%
“…26 We found that nadir Hb below 9.0 g/dL was associated with a higher risk of composite adverse events, even after stratifying patients by whether or not they received transfusions, what type of operation they had, or other confounders. This result suggests that above 9.0 g/dL may be the optimal Hb level for this population of patients, consistent with a previous report 27 that the inflection point in the incidence of composite outcomes lay around nadir Hb 9.0 g/dL for patients undergoing major vascular operation.…”
Section: Commentsupporting
confidence: 91%
“…Fluid resuscitation with red blood cells (RBCs) plays a fundamental role in maintaining tissue oxygenation during blood loss. This is particularly relevant for the vascular surgical patient because of frequent preoperative anemia 1,2 and surgical hemorrhage exceeding 500 mL, [3][4][5] both of which are associated with improved survival if RBC transfusion is initiated during surgery compared with no transfusion. 6 Furthermore, as these patients often present with cardiac disease, [7][8][9] they may be particularly vulnerable to a hemoglobin (Hb) level below 10 g/dL.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, as these patients often present with cardiac disease, [7][8][9] they may be particularly vulnerable to a hemoglobin (Hb) level below 10 g/dL. 2,10 However, as allogeneic RBC transfusions are also associated with mortality and cardiovascular morbidity, [11][12][13] and are an expensive and limited resource, randomized trials are warranted to balance risks and benefits of transfusion strategies in vascular surgery. 14 In other surgical specialties, it has been demonstrated that withholding transfusion until reaching a Hb level of 7.0 to 8.0 g/dL is safe, [15][16][17][18][19] but the majority of the evidence is based on postoperative stable patients.…”
Section: Introductionmentioning
confidence: 99%
“…La población que padece aneurismas aórticos generalmente está constituida por individuos de edad avanzada con comorbilidad, y durante estos complejos procedimientos pueden ocurrir hemorragias transoperatorias que requieran transfusiones sanguíneas [23][24][25][26] .Esta práctica ha sido estudiada en el escenario de intervenciones de revascularización de miembros inferiores por O'Keeffe, et al 27 ,quienes concluyen que los pacientes sometidos a derivaciones en los miembros pélvicos que recibieron al menos tres paquetes globulares tenían una razón de momios de 2.48 (intervalo de confianza del 95%: 1.55-3.98) mayor para desarrollar complicaciones posoperatorias que aquellos que no requirieron transfusiones. En 2017, Kougias, et al 28 analizaron 2508 procedimientos vasculares en 2106 pacientes durante un periodo de 8 años, y concluyeron que la anemia posoperatoria era un factor que incrementaba la mortalidad temprana y los eventos isquémicos, en particular en los pacientes con riesgo cardiovascular. Estos autores hacen énfasis en la necesidad de realizar ensayos clínicos controlados que aborden este dilema clínico, favoreciendo la restricción de transfusiones en los pacientes que se someten a cirugía vascular mayor.…”
Section: Figura 3 Gráfica Del Análisis De Kaplan-meier Para Comparar La Supervivencia De Los Pacientes Sometidos a Reconstrucción Aórticaunclassified